Pengaruh Kebijakan Harga Pembelian Pemerintah Beras Terhadap Pendapatan Petani Di Kecamatan Widasari Kabupaten Indramayu - Hasan, Sephia Alayda; Ismannudin; Soleh (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
Some farmers in Widasari District, Indramayu Regency, preferred to sell their rice harvests to middlemen rather than the Bulog, just because they wanted a commensurate selling price or even higher according to the expenses of farmers. In addition, other obstacles to limited access to Bulog, the slow process of absorption of crops, and incompatibility of absorption time with the harvest season. The purpose of this study is to determine the extent to which the rice HPP policy affects the income of farmers and how much influence it caused. The method used in this study is a quantitative method with a causal associative approach. The research sample was determined by the Cochran formula and produced 53 rice farmers respondents in Widasari District. Data collection techniques are carried out through the distribution of a questionnaire with a Likert scale, then analyzed using validity, reliability, simple linear regression tests, T tests, and the coefficient of determination with the assistance of the SPSS version 26 program. This is evidenced by the regression coefficient value of 0.389 and a significance level of 0.001 (<0.05). The value of the coefficient of determination (R²) shows that the HPP policy variable contributes to increasing farmers' income, although other factors such as production costs, land area, and market access also play an important role. The conclusion of this study is that the rice HPP policy plays a role in maintaining the stability of grain/rice prices and providing a more suitable revenue guarantee for farmers. However, the implementation of this policy in the field is still facing obstacles, such as strict Bulog quality requirements and limited access to farmers to sell their crops to Bulog.